TITONIA DAN JERAMI PADI YANG DIKOMPOSKAN TERHADAP CIRI KIMIA TANAH DAN PRODUKSI JAGUNG PADA ULTISOL - Gusnidar Gusnidar; Annisa Fitri; Syafrimen Yasin (Jurnal Solum, 2019)
Ultisol is broad suboptimal soils, need to be developed to increase for foods and animal feeds, but properties of physics and chemistry by the soils bad. This research was aimed to studied the influence of compost derived from titonia plus rice straw in improving chemical properties of Ultisol and corn production. This researh was conducted in glasshouse and Soil Laboratory of Agriculture Faculty, Andalas University, Padang, West Sumatra, Indonesia from January to July 2017. The experiment consisted of 5 treatments (0.00; 2.50; 5.00;7.50; 10.00 tonha-1. with 3 replications. Soil data resulted were compared to the soil criteria, while corn data were statistically analyzed the variance and continued using DNMRT at 0.05 level of significance, if F-calculated > F-table. The results of research showed that optimum dosage for repaired chemical properties of 7,50 tonha-1. It dosage soil pH 6,18 unit; available P by 17,64ppm; CEC by 18,38cmol(kg)-1; organic-C by 1,27%, total-N by 0,23%; K-exch. by 0,49cmol(kg)-1; Ca-exch. by 2,63  cmol(kg)-1; Mg-exch. by 0,57cmol(kg)-1 dan Na-exch. by 0,39cmol(kg)-1, with dry weight of seed by 85,48gpot-1; dry weight of straw by 75,84gpot-1 and dry weight of 100 seed by 25,50g. Key words : Compost derived from titonia plus rice straw, corn, Ultisol.